Human dermatophytoscs in Rio Grande do Sul (Brazil): 1988-1992 - Lopes, Jorge O.; Alves, Sydney H.; Benevenga, Jeni P. (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
The relative frequency of the dermatophytes in the central region of Rio Grande do Sul, Brazil, have changed during a survey carried out from 1988-1992. The frequency of the antropophilic species T. rubrum, T. mentagrophytes var. interdigitale and E.floccosum have decreased in comparison with the zoophilic species M. canis and T. mentagrophytes var. mentagrophytes. The relationship host/parasite and the low rate growth of dermatophytes in culture are discussed.